Evaluation of awareness and perception of plastic surgery among general public at a suburban teaching hospital - Parthasarathi, Karisni; Mahipathy, Surya Rao Rao Venkata; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Natarajan, Praveen Ganesh (International Surgery Journal, 2019)
Background: The general public is usually unaware of the available services of a plastic surgeon. Thus, we are trying to identify the perceptions of the public towards plastic surgery in a setting of a suburban tertiary teaching hospital by means of a questionnaire and the results were analyzed. Methods: 250 people took part in this study of varying ages, socioeconomic backgrounds, education levels and of either sex. These people were those visiting the different outpatient departments of our hospital. A short and simple questionnaire was devised in three languages of English, Tamil and Hindi. The questionnaires were analyzed and tabulated and the results were inferred. Results: 60.4% of the public think plastic surgery and cosmetic surgery are the same. 69.6% of the public think that plastic is used in plastic surgery. 90% of them think that there will be no scars following plastic surgery and that plastic surgery is only for the rich and famous. 39.6% of them think that plastic surgery is a risky operation whereas 30.4% feel that there is no risk involved. 80% of the population voted that a common procedure like rhinoplasty is done by a plastic surgeon. 70% of the public think that getting plastic surgery is good. All the public have heard the term plastic surgery, while 84.4% of them think that plastic surgery is only cosmetic surgery. 79.6% of the population has heard of plastic surgery from radio and television. Conclusions: There has been a sudden surge of plastic surgery performed over the recent years but the public are not much aware regarding these procedures and we must educate them for the speciality to progress.